Strengthening individual and family resilience against leprosy-related discrimination: A pilot intervention study. - Anna T Van't Noordende; Zoica Bakirtzief da Silva Pereira; Pritha Biswas; Mohammed Ilyas; Vijay Krishnan; Jayaram Parasa; Pim Kuipers (Public Library of Science (PLoS), 2021)
Background Leprosy and leprosy-related stigma can have a major impact on psychosocial wellbeing of persons affected and their family members. Resilience is a process that incorporates many of the core skills and abilities which may enable people to address stigma and discrimination. The current study aimed to develop and pilot an intervention to strengthen individual and family resilience against leprosy-related discrimination. Methodology We used a quasi-experimental, before-after study design with a mixed methods approach. The 10-week family-based intervention was designed to strengthen the resilience of individuals and families by enhancing their protective abilities and capacity to overcome adversity. The study was conducted in two sites, urban areas in Telangana state, and in rural areas in Odisha state, India. Persons affected and their family members were included using purposive sampling. Two questionnaires were used pre-and post-intervention: the Connor-Davidson Resilience Scale (CD-RISC, maximum score 100, with high scores reflecting greater resilience) and the WHOQOL-BREF (maximum score of 130, with higher scores reflecting higher quality of life). In addition, semi-structured interviews were conducted post-intervention. Data were collected at baseline, a few weeks after completion of the intervention, and in the Odisha cohort again at six months after completion. Paired t-tests measured differences pre- and post- intervention. Qualitative data were thematically analysed. Findings Eighty participants across 20 families were included in the study (23 persons affected and 57 family members). We found a significant increase in CD-RISC scores for persons affected and family members from Odisha state (baseline 46.5, first follow-up 77.0, second follow-up 70.0), this improvement was maintained at six-month follow-up. There was no increase in CD-RISC scores post-intervention among participants from Telangana state. WHOQOL-BREF scores were significantly higher at follow-up for persons affected in both states, and for family members in Odisha state. No families dropped out of the study. In the qualitative feedback, all participants described drawing benefit from the programme. Participants especially appreciated the social dimensions of the intervention. Conclusion This pilot study showed that the 10-week family-based intervention to strengthen resilience among persons affected by leprosy and their family members was feasible, and has the potential to improve resilience and quality of life. A large-scale efficacy trial is necessary to determine the effectiveness and long-term sustainability of the intervention.